Pengamatan Kegiatan Coal Getting PIT 2 di PT. Dayak Membangun Pratama, Kecamatan Kurun, Kabupaten Gunung Mas Provinsi Kalimantan Tengah - Putrawiyanta, I Putu; Ambeng, Rafvie Resido (Innovative: Journal Of Social Science Research, 2025)
PT Dayak Membangun Pratama is a company engaged in coal mining located in Tumbang Manyangan Village, Tumbang Tambirah, and Penda Pilang, Kurun and Tewah Districts, Gunung Mas Regency, located in Central Kalimantan with an area of 4,88.17 hectares of Borrowing Permit for Use of Forest Area (IPPKH) from the Ministry of Forestry with Decree (SK) Number 24/1/IPPKH/PMDN/2016 with an area of 999.95 hectares. The validity period of the production operation IUP is for 20 (twenty) years starting from November 29, 2011 to November 28, 2031. From the results of observations on seam B3, the time required for the coal getting activity was 4.19 hours with a coal volume of 125.99 tons. So that the productivity of coal getting on seam B3U[1] is 30.07 tons/hour. On seam B1 and Fault B1, the time required for coal getting activities is 3,143 hours with a coal volume of 134.5 tons. So that the productivity of coal getting on seam B1 and Fault B1 is 42.8 tons/hour. In the B23L seam, B23U fault and B3U fault, the time required for coal getting activities is 5.57 hours with a coal volume of 167.62 tons. So the productivity of coal getting on seam B23L, Fault B23U and Fault B3U is 30.01 tons/hour.